Equity and trusts - TANG, Hang Wu (Institutional Knowledge at Singapore Management University, 2022)
OOPA Pte Ltd v Bui Sy Phong1 dealt with the complex interplay between equity and company law. The plaintiff company, OOPA Pte Ltd (“OOPA”), was a Singapore company set up for the purpose of holding a Vietnamese operating company, OnOnPay Vietnamese Mobile Services JSC (“OnOnPay”). This was a start-up venture to provide Vietnamese mobile subscribers the opportunity to top up mobile airtime and an e-wallet application for small retailers in Vietnam. B